2022
DOI: 10.1186/s12961-022-00814-5
|View full text |Cite
|
Sign up to set email alerts
|

Methodological pluralism for better evaluations of complex interventions: lessons from evaluating an innovation platform in Australia

Abstract: Complex interventions, such as innovation platforms, pose challenges for evaluators. A variety of methodological approaches are often required to build a more complete and comprehensive understanding of how complex interventions work. In this paper, we outline and critically appraise a methodologically pluralist evaluation of an innovation platform to strengthen primary care for Aboriginal and Torres Strait Islander Australians. In doing so, we aim to identify lessons learned from the approach taken and add to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The multi-dimensionality of healthcare indicated that exploring the definition of healthcare quality necessitated a pluralistic approach, which applies more than one methodology [ 21 ]. This was represented through the three approaches used to allow a more holistic perspective [ 21 , 22 ] of the definition of quality in healthcare. This study was registered with the National Medical Research Registry (NMRR-19-3522-50 030) and approved by the Medical Research and Ethics Committee (MREC), MOH Malaysia.…”
Section: Methodsmentioning
confidence: 99%
“…The multi-dimensionality of healthcare indicated that exploring the definition of healthcare quality necessitated a pluralistic approach, which applies more than one methodology [ 21 ]. This was represented through the three approaches used to allow a more holistic perspective [ 21 , 22 ] of the definition of quality in healthcare. This study was registered with the National Medical Research Registry (NMRR-19-3522-50 030) and approved by the Medical Research and Ethics Committee (MREC), MOH Malaysia.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the inclusion of different study designs resulted in inconsistencies in the quality appraisal as three separate tools had to be used. However, not limiting by study design was justified as it facilitated methodological pluralism which is useful, not only for neutralising the limitations inherent in a single method, but also for gaining a more holistic analysis that is not achievable through the use of just one study design [79]. The narrative synthesis approach is often critiqued for lacking transparency [80] and an in-depth description of the process was beyond the scope of this review.…”
Section: Limitationsmentioning
confidence: 99%